2019
DOI: 10.1038/s41418-019-0321-x
|View full text |Cite
|
Sign up to set email alerts
|

FGFR4 phosphorylates MST1 to confer breast cancer cells resistance to MST1/2-dependent apoptosis

Abstract: Cancer cells balance with the equilibrium of cell death and growth to expand and metastasize. The activity of mammalian sterile20-like kinases (MST1/2) has been linked to apoptosis and tumor suppression via YAP/Hippo pathway-independent and -dependent mechanisms. Using a kinase substrate screen, we identified here MST1 and MST2 among the top substrates for fibroblast growth factor receptor 4 (FGFR4). In COS-1 cells, MST1 was phosphorylated at Y433 residue in an FGFR4 kinase activity-dependent manner, as assess… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 78 publications
0
28
0
Order By: Relevance
“…Mutated FGFR4 was found to induce local growth and enhance metastasis in these cancers [23]. In breast cancer, FGFR4 resist cancer cell apoptosis by phosphorylating MST1 [24]. Hence, FGFR4, owing to the oncogenic activity, may serve as a potential predictive biomarker for anti-FGFR4 targeted therapy [25].…”
Section: Introductionmentioning
confidence: 99%
“…Mutated FGFR4 was found to induce local growth and enhance metastasis in these cancers [23]. In breast cancer, FGFR4 resist cancer cell apoptosis by phosphorylating MST1 [24]. Hence, FGFR4, owing to the oncogenic activity, may serve as a potential predictive biomarker for anti-FGFR4 targeted therapy [25].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Previous studies have reported that MOB1 expression might have great influence on the progression of some malignant tumors such as pancreatic cancer and breast cancer; however, whether it could affect the development of CRC still has not been studied. 16,17 In this study, MOB1 expression was found remarkably upregulated in CRC tissues and cell lines. In addition, we found that patients with low MOB1 expression had higher metastasis incidence and pathological stage and lower progression-free survival rate, suggesting a worse prognosis.…”
Section: Discussionmentioning
confidence: 53%
“…15 Recent studies have suggested that MOB1 may be engaged in the regulation of proliferation, apoptosis, migration and invasion of pancreatic cancer, breast cancer and other malignant tumor cells. 16,17 Therefore, the study of MOB1 in CRC not only helps to clarify the pathogenesis of this tumor but also provides valuable targets for its diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, higher doses greatly increase Hippo expression and cause YAP phosphorylation, triggering lens fiber differentiation [128]. Another study investigating the mechanism underlying breast cancer cell resistance to MST1/2-dependent apoptosis showed that FGFR4 phosphorylates MST1/2 and inhibits its activation [129].…”
Section: Receptor Tyrosine Kinases Vegfr Tie and Fgfr Regulate Angiomentioning
confidence: 99%
“…Reduced MST1/2 phosphorylation by VEGFR and YAP/TAZ effect on VEGFR-induced angiogenesis [118] Effect of actin cytoskeleton dynamics on YAP/TAZ through VEGFR2-SFKs-Rho GTPase [119] Tie (Altiratinib) YAP1/STAT3 complex regulate ANG2 expression promoting angiogenesis [121] YAP-dependent expression of ANG2 is regulated by cellular confluency [122] YAP/TAZ knockdown decreases Tie2 expression and blocks vascular formation [123] FGFR (erdafitinib, Infigratinib) FGF2-SAPK/JNK MAP kinase signaling downregulates TAZ [124] YAP/TBX5 complex controls FGFR1, -2, and -4 expression and FGF5 reduces LATS cellular levels [126] FGF1/FGFR3, MAPK/ERK mediated, increase of ETV5 elevates TAZ activity [127] Different doses of FGF have different effects on hippo and cause distinct outcomes in lens cells [128] FGFR4 mediated breast cancer cell MST1/2 resistance [129] Direct phosphorylation of YAP by FGFR, RET, and MERTK receptors [130] ALK (crizotinib, brigatinib) ALK inhibits LATS and activates YAP to drive tumorigenesis phenotype [132]…”
Section: Egfr (Gefitinib Erlotinib)mentioning
confidence: 99%